HUBUNGAN JUMLAH PERDARAHAN DENGAN KEJADIAN HIPOTENSI PADA PASIEN SECTIO CAESARIA DENGAN SPINAL ANESTESI DI RSI UNISMA MALANG - Paryadi Paryadi; Ardhiles Wahyu Kurniawan; Sindu Sintara; Widigdo Rekso Negoro (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Background: Cesarean section can lead to bleeding, which can reduce intravascular volume and result in a decrease in cardiac output. If this condition is not promptly addressed, it can trigger hypotension. Maternal mortality rates increase by 40-80% due to bleeding during cesarean section deliveries. The aim of this study is to determine the relationship between the amount of bleeding and the occurrence of hypotension in patients undergoing spinal anesthesia for cesarean section at RSI Unisma Malang. Method: An analytical observational study using a cross-sectional method. The total sample size was 26 patients, and data were obtained through direct observation with documentation following the informed consent procedure. Sample selection was done using purposive sampling technique. Univariate statistical analysis was followed by Spearman’s rho statistical test. Results: There is a very strong correlation between the amount of bleeding and the occurrence of hypotension in patients undergoing cesarean section with spinal anesthesia at RSI Unisma Malang (p= 0.000 < α 0.05; r = 0.902). Conclusion: There is a very strong positive correlation between the amount of bleeding and the occurrence of hypotension, meaning that higher amounts of bleeding can lead to a decrease in blood pressure (hypotension). Keywords: Hypotension, Amount of bleeding, Sectio Caesaria, Spinal anesthesia